The Future of Work: Super-Exploitation and Social Precariousness in the 21st Century - Smith, Murray E. G. (Labour / Le Travail, 2017)
The article reviews the book, "The Future of Work: Super-Exploitation and Social Precariousness in the 21st Century," by Adrián Sotelo Valencia.